Arduous tasks : Primo Levi, translation, and the transmission of Holocaust testimony - Insana, Lina N., 1970- (Toronto Italian studies., 2009)
In Arduous Tasks, Lina N. Insana demonstrates how translation functions as a metaphor for the transmission of Holocaust testimony and broadens the parameters of survivor testimony.